Pengembangan Media Pembelajaran Berbasis Website "Jagat Kawruh" Menggunakan Model Problem Based Learning Pada Mata Pelajaran Informatika - Savana Putra Aditama; Rindu Puspita Wibawa; I Gusti Lanang Putra Eka Prismana; Mohammad Wildan Habibi (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Monotonous Computer Systems learning in vocational high schools often causes student boredom and hinders collaboration monitoring. To address this, this study developed the "Jagat Kawruh" educational website integrating Problem Based Learning (PBL) and gamification. Utilizing the Research and Development (R&D) ADDIE model, the media features an interactive maze game quiz to boost motivation. The trial involved 36 tenth-grade Software Engineering students at SMKN 2 Buduran. Expert validations confirmed the product is highly valid (media 87.22%, material 95.45%, teaching module 94.58%, evaluation 94.44%). Effectiveness tests revealed a significant improvement in conceptual understanding (Paired Sample t-Test p < 0.001) with an N-Gain of 0.49 (moderate). Furthermore, the User Experience Questionnaire (UEQ) results showed positive evaluations, peaking in the Stimulation scale (1.81/Excellent). In conclusion, "Jagat Kawruh" is proven valid, practical, and effective in facilitating interactive and independent PBL learning.